Effect of Single-dose Azithromycin on Pneumococcal Carriage and Resistance: A Randomized Controlled Trial. Issue 9 (23rd May 2022) - Coulibaly, Boubacar; Kiemde, Dramane; Zonou, Guillaume; Sié, Ali; Dah, Clarisse; Bountogo, Mamadou; Brogdon, Jessica; Hu, Huiyu; Lebas, Elodie; Porco, Travis C.; Doan, Thuy; Lietman, Thomas M.; et al.
Abstract : We evaluated antibiotic resistance selection in Streptococcus pneumoniae isolates from children participating in an individually randomized trial of single-dose azithromycin versus placebo. After 14 days, the prevalence of resistance to erythromycin, oxacillin, and clindamycin was elevated in the azithromycin versus placebo group. There was no difference at 6 months.